A critical analysis of the sermon as an educational space in the Church - Piter, Yan (Educenter : Jurnal Ilmiah Pendidikan, 2024)
In the context of religious education, the effectiveness of sermons can be measured by how well the congregation can understand, remember, and apply the teachings delivered. Aspects such as the quality of delivery, the use of easy-to-understand language, the relevance of the topic to the congregation's life, and the frequency of attendance at services can be important factors that influence learning outcomes. This study explores the influence of Sermon Quality and Frequency of Congregation Attendance on Congregation Understanding and Knowledge in Tanah Toraja churches. Using the Structural Equation Modeling Partial Least Squares (SEM-PLS) method, this model testing was carried out to see the value of R Square, Q2, Model Fit, and the test of influence between variables, this study analyzed data obtained from a sample of 144 congregations selected purposively. The results showed that both sermon quality and frequency of attendance had a significant influence on increasing congregational understanding and knowledge, with sermon quality having a more dominant influence. These findings underscore the importance of high-quality sermon delivery and consistent congregational attendance to support a deeper understanding of religion. Based on these results, it is recommended that churches improve training for preachers and create an environment that encourages regular congregational attendance, in order to strengthen their religious knowledge and understanding.